Potential impact of extra education on the development of executive functions within a year in preschool children: an exploratory research - Dolgikh, Alexandra; Bayanova, Larisa; Chichinina, Elena (Frontiers in Psychology, 2023)
Executive functions have been shown to develop through various extra classes in preschool age. But the optimal for executive functions development system of such classes has not yet been explored. The present exploratory study aimed to examine the difference in the executive functions development within a year between children attending the system of extra classes (music, choreography, art, foreign language, literacy, math, computer science, and science) twice a week for 4 h in a preschool education center and children who did not take no extra classes. There were 60 children who attended extra classes and 64 children who did not take extra classes. In each group, approximately 17% were boys. The first assessment of executive functions was performed in the penultimate year of kindergarten, when the children were 5–6 years old. The second was performed 1 year later. The executive function level was assessed using NEPSY-II subtests “Inhibition,” “Statue,” “Memory for Designs,” “Sentences Repetition,” and “Dimensional Change Card Sort.” Mothers also reported about their children’s attendance in extra classes, their children’s screen time, the level of maternal education, and the level of family income. The study revealed that children attending the system of the extra classes showed a higher verbal working memory development within a year than the children taking no extra classes. The obtained data plays an important role for the design of further research of the topic and for the practical recommendations for parents and teachers.